Tureccy i bałkańscy „singers of tales” – „jarzmo” inspiracji czy epicka dwubiegunowość? - Agnieszka Ayşen Kaim (Slavia Meridionalis, 2015)
Turkish and Balkan “singers of tales” – a yoke of inspiration or epic independence? The research material is mostly based on the works of Albert Lord and Milman Parry, Karl Reichl, Ilhan Basgoz, Pertev Boratav. Epic singers played a significant part in spreading national spirit, be it Turkish or Slavic. The Balkan artists called guslar used a one-string instrument called gusle while a Turkish minstrel ozan and ashik usually used a two-stringed instrument called kopuz or saz. The typical stage for their activities were coffeehouses. Oral epics were transmitted by word of mouth from one singer to another, sometimes by way of formal training based on the transmission of repertoire and technique from master to apprentice. Representative of both traditions was the use of metrics and formulaic style. The song was orally composed in performance, with the audience’s participation. The musical aspect facilitated memorisation. The text to be learned by heart was a story in a song. Although the Turkish and Balkan epic traditions developed independently of each other, the effect of Turkish conquest on the Balkan epic tradition is evident, especially in the style of those singers who perform in borderland (in Kosovo and northern Albania). The Turkish occupation itself became the subject of many epics, reinforcing the national identity of the local population. However, oriental influences also emerged in some formal characteristics, such as the length of the songs, the ornamentation and stylised oriental images and the transformation of separate ballads and short narratives into epic cycles. In both cases for performers themselves this artistic activity became “a way of life”.